Software quality : methods and tools for better software and systems : 10th International Conference, SWQD 2018, Vienna, Austria, January 16-19, 2018, Proceedings /: methods and tools for better software and systems : 10th International Conference, SWQD 2018, Vienna, Austria, January 16-19, 2018, Proceedings. (2018) - Unknown
No abstract available